Aptitude of different softwoods and hardwoods to drying with superheated steam. Drying end point determination - Alvarez Noves, H.; Fernandez-Golfin, J. I. (Forest Systems, 1993)
Drying with superheated steam is evaluated in lumber from different Spanish softwoods (Pinus pinaster, radiata, sylvestris and nigra) and hardwoods (Eucalyptus globulus and Populus sp.). Major problems with the softwoods seems to be related with high resin content and encased knots. Problems with hardwoods drying are related with permeability, collapse and checking tendency. The applicability of the determination of the internal wood temperature to decide the end point of drying is also evaluated.